Phase II study of induction chemotherapy with docetaxel, cisplatin, 5-fluorouracil followed by radioimmunotherapy with cetuximab and intensity-modulated radiotherapy in combination with a carbon ion boost for locally advanced tumors of the oro-, hypopharynx and larynx - Hauswald, Henrik; Jensen, Alexandra; Krauß, Jürgen; Haselmann, Renate; Lossner, Karen; Münter, Marc; Debus, Jürgen (Clinical and translational radiation oncology, 2018)
Purpose: This phase II trial was designed to evaluate efficacy and safety of a highly intensified therapy in locally advanced squamous cell carcinoma of the oro-, hypopharynx and larynx. Methods: In this prospective, mono-centric, open-label, non-randomized phase II trial the single treatment arm consisted of a combined induction chemotherapy with docetaxel, cisplatin, 5-fluorouracil, followed by bioradiation with the monoclonal antibody cetuximab, carbon ion boost (24Gy(RBE) in 8 fractions) and IMRT (50Gy in 25 fractions). The trial was closed early due to slow accrual. Results: Eight patients (median age 52.5years) were enrolled into the trial. The median follow-up was 13months and the 12-months locoregional tumor control, progression-free survival and overall survival rates were 100.0% each. Complete remission was achieved in 7 patients. The most commonly late radiation adverse event was xerostomia (85.7% at 12months). Five serious adverse events with recovery were documented in 4 patients: mucositis grade 3 (n=2), decreased lymphocyte count grade 4, febrile neutropenia grade 4 and hypersensitivity grade 3 to cetuximab (n=1 each). Most symptom scales had their worst value at the last treatment day and recovered until the 4th follow-up visit. Conclusion: The study treatment was tolerable and promising. Reduced quality of life recovered for most aspects until the last follow-up visit.